1958
DOI: 10.1152/ajplegacy.1958.192.2.392
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia Excretion of the Guinea Pig and Rabbit

Abstract: During fasting in guinea pigs a marked drop of ammonia excretion parallel to a drop in titratable alkalinity was observed. Feeding of cabbage increased ammonia excretion in excess of the titratable alkalinity. In acute studies in guinea pigs and rabbits after administration of saline, bicarbonate or hydrochloric acid, a depression of ammonia excretion was consistently observed whenever the urinary pH was close to neutrality, while in acid as well as in alkaline urines an increase in ammonia excretion occurred.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1958
1958
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…The rate at which 'ammonia' is produced most likely depends upon the supply of glutamine (and other precursors) and upon the activity of the intracellular enzymes, so that it might be affected by intracellular pH. The use by Orloff & Berliner (1956) and by Richterich et al (1958) of the term 'production-limited' to describe the excretion of 'ammonia' when its rate was not increased by increasing the rate of flow of urine might appear to imply that all the 'ammonia' produced by the kidneys was excreted in the urine. In fact it is probable that, even under conditions in which the excretion of 'ammonia' has been regarded as 'production-limited', more 'ammonia' may leave the kidneys in the renal venous blood than in the urine, so that the rate of urinary excretion ought not to be regarded as limited primarily by production.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate at which 'ammonia' is produced most likely depends upon the supply of glutamine (and other precursors) and upon the activity of the intracellular enzymes, so that it might be affected by intracellular pH. The use by Orloff & Berliner (1956) and by Richterich et al (1958) of the term 'production-limited' to describe the excretion of 'ammonia' when its rate was not increased by increasing the rate of flow of urine might appear to imply that all the 'ammonia' produced by the kidneys was excreted in the urine. In fact it is probable that, even under conditions in which the excretion of 'ammonia' has been regarded as 'production-limited', more 'ammonia' may leave the kidneys in the renal venous blood than in the urine, so that the rate of urinary excretion ought not to be regarded as limited primarily by production.…”
Section: Resultsmentioning
confidence: 99%
“…Dependence of the rate of excretion of 'ammonia' upon urine flow has been well established in animals other than man. Richterich, Goldstein & Dearborn (1958) demonstrated a linear relation between minute volume and the output of urinary 'ammonia' in guineapigs and rabbits. These animals are herbivora, whose urine is usually alkaline (Claude Bernard, 1865), but Orloff & Berliner (1956) found that the excretion of 'ammonia' was proportional to minute volume in dogs also if the rates of flow were small enough and if the urine was made alkaline.…”
mentioning
confidence: 94%
“…during states of diabetic ketoacidosis, renal ammonia excretion in creases 10-fold. The importance of this re sponse in mammalian acid-base regulation is best exemplified by a comparative exam ination of mammalian species [38,61]. The rabbit, having a relatively low capacity for renal ammonia excretion (10 pmol/kg • h), is unable to withstand small doses of acids easily tolerated by other mammals, such as the dog, which are characterized by a greater rate of renal ammonia excretion (130 pmol/kg • h).…”
Section: Ammoniamentioning
confidence: 99%
“…The metabolic use of VFA’s, coupled with the intake of an alkaline ash diet, eliminates the non-volatile acidic burden on the kidneys of this species. The excretion of nutrient alkali, along with the net secretion of bicarbonate by the β-intercalated cells in the cortical collecting ducts (CCD), gives normal rabbit urine its unique acid-base characteristics, which include a high titratable alkalinity, a pH in the zone of 8 ± 0.4, a milky appearance due to the precipitation of calcium salts at alkaline pH, and trace concentrations of ammonia ( Richterich et al, 1958 ; Walsh and O'Donovan, 2019a ).…”
Section: Introductionmentioning
confidence: 99%